The Fire and the Rain - Girish Karnad (New Delhi Oxford University Press, 1998)
This play by one of India's foremost playwrights and actors is based on a story from the Mahabharata which tellingly illuminates universal themes - alienation, loneliness, love, family, hatred - through the daily lives and concerns of a whole community of individuals.